Evaluation of leucaena populations for tolerance to aluminum - Maluf, Angela Maria (2014)
This paper aimed at verifying the existence of genetic variability in nutrient solution for aluminum tolerance among 29 populations of Ieucaena (Leucaena Ieucocephala (Lam.) de Wit.), tested under five different AI concentrations (0, 3, 6, 9 and 12 ppm) in two glasshouse experiments, and at classifying these populations according to their tolerance to AI. The traits under study in the classification of the populations for their AI tolerance were: length of the aerial portion (Y1), length of the longest root (Y2), dry weight of aerial portion (Y3), dry weight of roots (Y4), length of the first leaf (Y5), number of lateral branches (Y6), dry weight of the aerial portion/dry weight of roots ratio (Y7) and cotyledon persistence (Y8). The examination of the standardized means for the eight traits (Y1 to Y8) under the five AI concentrations over two experiments was able to screen populations T-1, T-2, T-3 and T-14 as being tolerant to AI, and T-4, T-5, T-12 and T-22 as being intolerant. The remaining populations showed variable results, depending on the trait considered. Since there is no previous information about the traits which are the most appropriate to screen for AI tolerance, the classification of these remaining 21 populations as tolerant/intolerant is inconclusive.